2010
DOI: 10.1021/jm901890s
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrophobic Substituents on the Terminal Nitrogen of Histamine in Receptor Binding and Agonist Activity: Development of an Orally Active Histamine Type 3 Receptor Agonist and Evaluation of Its Antistress Activity in Mice

Abstract: The terminal nitrogen atom of histamine was modified with lipophilic substituents to investigate the structure-activity relationship of histamine type 3 receptor (H3R) agonists. The introduction of an alkylated benzene rings maintained or increased the H3R binding affinity. The most potent compound, 4-(2-(4-tert-butylphenylthio)ethyl)-1H-imidazole, possessed in vivo agonistic activity, decreasing brain N(tau)-methylhistamine levels in mice after oral administration. It also exhibited antistress activity in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…It was identified as a potent H 3 R agonist with good selectivity over H 1 R (20‐fold) and H 4 R (93‐fold). Particularly, ( S )‐enantiomer 186 was favorable for binding with the hydrophobic region in TM6 and exhibited much higher affinity (13‐fold) than ( R )‐enantiomer . These observations indicated that human H 3 R receptor recognized the strictly enantiomeric structure of ligands.…”
Section: Imidazoles As Antihistaminic Agentsmentioning
confidence: 90%
“…It was identified as a potent H 3 R agonist with good selectivity over H 1 R (20‐fold) and H 4 R (93‐fold). Particularly, ( S )‐enantiomer 186 was favorable for binding with the hydrophobic region in TM6 and exhibited much higher affinity (13‐fold) than ( R )‐enantiomer . These observations indicated that human H 3 R receptor recognized the strictly enantiomeric structure of ligands.…”
Section: Imidazoles As Antihistaminic Agentsmentioning
confidence: 90%
“…(Kitbunnadaj et al, 2005). Other lipophilic agonists have also been described in an extensive SAR study (Govoni et al, 2006), and an agonist (37) (human H 3 receptor K i = 0.17 nM, 77% efficacy) was active in vivo in mice in blocking aggression and stress (Ishikawa et al, 2010). Other H 3 receptor agonists have been described with novel structural variations, including immethridine (human H 3 receptor K i = 0.9 nM, 90% agonist efficacy), an analog of immepip wherein the highly basic piperidine moiety is replaced by a less basic pyridinyl moiety (Kitbunnadaj et al, 2004).…”
Section: E H 3 -Selective Ligandsmentioning
confidence: 98%
“…Imidazole-containing agonists have shown some potential application in different therapeutic areas, such as mechanical nociception, 23 obesity, and diabetes mellitus (diet-induced obesity mice test) 24 and stress (rodent-intruder mice test). 21 Some data also support the hypothesis of cardioprotective effect of H 3 R receptor activation. 25,26 However, it is fair to say that imidazole-containing agonists may suffer from the same imidazole-related drawbacks that were associated with the first generation of imidazole-containing H 3 R antagonists (vide supra).…”
Section: Introductionmentioning
confidence: 64%
“…In sharp contrast, developing non-imidazole H 3 R agonists has not been very successful. The best agonists contain an imidazole ring and, compared to the endogenous ligand histamine ( 1 ), these derivatives show similar [e.g., imbutamine ( 2 )] or significantly higher affinity (p K i ) and/or functional activity (pEC 50 ) on H 3 R [e.g., imetit ( 3 ), methimepip ( 4 ), and (1 S ,2 S )-2-(2-aminoethyl)-1-(1 H -imidazol-4-yl)­cyclopropane ( 5 )] (Figure A). Imidazole-containing agonists have shown some potential application in different therapeutic areas, such as mechanical nociception, obesity, and diabetes mellitus (diet-induced obesity mice test) and stress (rodent-intruder mice test) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation